APLIKASI E-RESOURCES PERPUSTAKAAN DALAM PENUNJANG PENINGAKATAN KINERJA PADA LAYANAN KATALOG DIGITAL ONLINE - Guidio Leonarde Ginting; Fahmy Syahputra (STMIK Budi Darma, 2017)
As one of the supporting facilities in the learning process in the library universities provides a very important service for educational learners. The functions of libraries are Storage, Education, Research, Information, and Cultural Recreation, as stipulated in Government Regulation number 24 of 2014. As a center of scientific information providers required by learners, libraries are required to provide accurate information quickly and efficiently. During this time at STMIK Budi Darma library in providing its service is still traditional. With an area of 96 square meters (m2) and filled with a total of 11,755 library collections will certainly require a lot of cabinets and shelves to accommodate the collection contained in the library. This will certainly greatly affect the library services in serving the demand of learners in accessing the information contained in the library. On the basis of this it is necessary to develop the traditional library system into a computer-based application that is able to provide library catalog information in digital form known as e-Resource. The e-Resource application of STMIK Budi Darma Library is expected to improve the service performance of the library in providing digital information online in the form of library catalogs stored digitally quickly, precisely and accurately.